2010
DOI: 10.1111/j.1532-5415.2010.02820.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance Measures Predict Onset of Activity of Daily Living Difficulty in Community‐Dwelling Older Adults

Abstract: OBJECTIVES-To assess the predictive value of five performance-based measures for the onset of difficulty in basic activities of daily living (ADL).DESIGN-A prospective cohort study; home visits every 6 months for 18 months. SETTING-Community-basedPARTICIPANTS-Community-dwelling older adults, n=110, (mean age, 80; SD, 7.0; range, 67-98 years) who reported no difficulty in basic ADLs. MEASUREMENTS-TheShort Physical Performance Battery (SPPB), gait speed, Berg Balance Scale (BBS), grip strength, and Timed Up & Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(125 citation statements)
references
References 30 publications
7
111
0
6
Order By: Relevance
“…A recent study has documented a different threshold (less than 12 kg for grip strength) for experiencing difficulties in accomplishing activities of daily living in older women [50]. A possible explanation may be that individuals with adult-onset DM1 adapt progressively to their disease and do not see their difficulties anymore (in our sample, most people had the disease for more than 20 years).…”
Section: Rehabilitation Referral Criteria For Housing-related Activitiesmentioning
confidence: 80%
“…A recent study has documented a different threshold (less than 12 kg for grip strength) for experiencing difficulties in accomplishing activities of daily living in older women [50]. A possible explanation may be that individuals with adult-onset DM1 adapt progressively to their disease and do not see their difficulties anymore (in our sample, most people had the disease for more than 20 years).…”
Section: Rehabilitation Referral Criteria For Housing-related Activitiesmentioning
confidence: 80%
“…Physical performance measures are increasingly an integral part of clinical care for older adults, particularly in the rehabilitation setting, because they have good predictive value of subsequent health and functional independence [20]. Performance measures of mobility, aerobic endurance, and strength have all been identified as important indicators of health and have been studied for the prediction of activities of daily living (ADL) disability, mobility disability, and mortality [2125]. In this study, we seek to replicate and extend previous research by examining both self-reported physical function, which reflects the extent to which functional impairments affect daily activities, and performance-based measures of functional status, including mobility, strength, and aerobic endurance.…”
Section: Introductionmentioning
confidence: 99%
“…Com o avanço da idade, ocorre um declínio na massa magra, responsável por uma perda significativa de força que ocasiona limitações na independência funcional e, consequentemente, na realização das atividades de vida diária (AVDs) 1 . Tais limitações acarretam, também, a redução de sua qualidade de vida 4 , visto que a capacidade de realizar as atividades comuns de vida diária sem necessidade de ajuda de outra pessoa mostra-se essencial para a manutenção da qualidade de vida 5 .…”
Section: Introductionunclassified
“…Medidas de desempenho físico, incluindo medidas de mobilidade, equilí-brio e força, tem sido investigadas em relação ao seu valor preditivo para futura incidência de dependência em atividades da vida diária e incapacidade 5,8 . Com isso, identificar indivíduos com tais déficits pode auxiliar na detecção de um declínio funcional de forma precoce, o que possibilita um processo de intervenção de maneira otimizada 5 .…”
Section: Introductionunclassified
See 1 more Smart Citation